Археологічні обстеження у пониззі Сухого Кобелячка на Полтавщині - Супруненко, О.Б.; Шерстюк, В.В. (Археологічні дослідження в Україні, 2009)
The results of the archaeological prospecting in mouth of the Sukhyi Kobelyachok River in Kremenchuk Region of Poltava Oblast are published. 138 barrows of 22 barrow groups and 9 separate mounds are discovered. On and near the barrows 9 anthropomorphic stelae of the Copper Age and the Bronze Age, as well as stone tombs of the 18th—19th c. Cossacks’ cemeteries, were found.